ВПЛИВ МОДИФІКАЦІЇ АЛМАЗНИХ ЧАСТИНОК КАРБІДОУТВОРЮЮЧИМИ ПОКРИТТЯМИ НА ВЛАСТИВОСТІ АЛМАЗНИХ КОМПОЗИТІВ - Вєніков, Владислав (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2025)
The article reviewing effect of coating the surface of diamond powders with titanium boron and chromium on the properties of diamond polycrystals sintered under high pressure and temperature.